Calculation of a thermoelectric unit as part of a system for conducting thermal physiotherapy procedures - O. V. Evdulov; M. A. Khazamova; U. I. Abdulkhakimov; I. Yu. Gamzalova; I. A. Gabitov (Вестник Дагестанского государственного технического университета: Технические науки)
Objective.  The aim of the study is to consider the methodology for calculating a thermoelectric unit as part of a thermoelectric system (TPS) intended for thermal exposure in medical practice, as well as the results of a numerical experiment carried out using it.Method. The calculation model of the thermoelectric block, which is part of the system for conducting thermal physiotherapy procedures, is described. The model is built on the basis of standard expressions for calculating the electrical and geometric parameters of thermoelectric modules (TEM) depending on the thermal and electrical parameters of thermoelement (FC) materials, heat and cooling capacity values, and characteristics of heat removal systems from FC hot junctions.Result. According to the calculation model, the thermoelectric unit was calculated, which is part of the system for conducting thermal cosmetic procedures, developed in the laboratory of semiconductor thermoelectric devices and devices of the Daghestan State Technical University on the temperature difference between the junctions for different values of the supply current, as well as the dependence of the voltage on the TEM on the magnitude of the supply current at different values of the temperature difference between the junctions, the change in temperature at the cold junction and the power of the TEM on the supply current. The graphs are calculated at a hot junction temperature of 320 K.Conclusion. As a result of calculations, it was found that the operating power range of TEMs of the TV-127-1.4-2.5 type is in the range from 8 to 17 W with an average temperature difference between the junctions of 45 K. In this case, the supply current will be 1 .5-3.5 A with a power consumption of 20 to 80 watts. The refrigerating coefficient varies from 0.1 to 0.5. In accordance with the tasks to be solved, the thermoelectric unit of the device should include four TEMs of this type.